Mobile Media SPL creation by Feature IDE using FODA (Global Journal of Computer Science and Technology, 2014)
Software Product Lines are used in many areas, combining to form new technologies and products. A product line is a group of products that share a common development platform and vary by the composition and implementation method for the functionalities. This paper describes the implementation or creation of MobileMedia feature model using FODA (Feature Oriented Domain Analysis) methodology using FeatureIDE eclipse plug-in. The feature model created in this depicts various outlines as feature model as visual model, collaboration diagram view of model, its configuration, FeatureIDE Statistics. Basically the paper shows the concept how SPLs can be viewed as feature diagrams using various tools in order to deal with them. This modelling has been widely used by software product line communities and a number of extensions have been proposed.
Keywords: featureide; feature model; mobilemedia; SPLS